A contemporary review of therapeutic and regenerative management of intracerebral hemorrhage. Issue 11 (14th October 2021) - Sadaf, Humaira; Desai, Virendra R.; Misra, Vivek; Golanov, Eugene; Hegde, Muralidhar L.; Villapol, Sonia; Karmonik, Christof; Regnier‐Golanov, Angelique; Sayenko, Dimitri; Horner, Philip J.; Krencik, Robert; Weng, Yi Lan; et al.
Abstract: Intracerebral hemorrhage (ICH) remains a common and debilitating form of stroke. This neurological emergency must be diagnosed and treated rapidly yet effectively. In this article, we review the medical, surgical, repair, and regenerative treatment options for managing ICH. Topics of focus include the management of blood pressure, intracranial pressure, coagulopathy, and intraventricular hemorrhage, as well as the role of surgery, regeneration, rehabilitation, and secondary prevention. Results of various phase II and III trials are incorporated. In summary, ICH patients should undergo rapid evaluation with neuroimaging, and early interventions should include systolic blood pressure control in the range of 140 mmHg, correction of coagulopathy if indicated, and assessment for surgical intervention. ICH patients should be managed in dedicated neurosurgical intensive care or stroke units where continuous monitoring of neurological status and evaluation for neurological deterioration is rapidly possible. Extravasation of hematoma may be helpful in patients with intraventricular extension of ICH. The goal of care is to reduce mortality and enable multimodal rehabilitative therapy.